Two new species of Acantholaimus (Nematoda, Chromadoridae) from the deep southeastern Atlantic (Santos Basin) - Manoel, Alex; Esteves, André Morgado; Neres, Patrícia Fernandes (Zootaxa, 2022)
Two new species of the genus Acantholaimus (Nematoda, Chromadoridae) are described from the South Atlantic, in the Santos Basin off the slope of southeastern Brazil. Acantholaimus pugious sp. n. is characterized by a narrow and elongated anterior end; teeth that are thin and long stylet-like (two in number), amphidial fovea located far from the anterior end and occupying most of the corresponding body diameter. Acantholaimus bidentatus sp. n. is characterized by a narrow anterior end, cuticle with more evident dots on both body extremities (up to amphidial fovea and tail); two long, protractible thin teeth (similar to stylet), with curved proximal part. The two species are similar in the shape of the teeth. The teeth morphology may be correlated to the process of adaptive convergence of these species. An emended diagnosis of the genus is provided.